EKSPLORASI POTENSI UMKM PELINGGIH STYLE BALI: STUDI KASUS PENERAPAN STRATEGI PEMASARAN DIGITAL - Purwaningrat, Putu Atim; Putu Krisna Devy, Ida Ayu; Krisna Kepakisan, Ngurah; Bagus Denix Saputra, I Putu; Made Githa Cahyadi, I Gusti (Dharma Bhakti, 2025)
Pelinggih Gaya Bali, which is part of the Balinese Hindu tradition, has great potential to be developed as a cultural product with high economic value. This research aims to explore the market potential of Pelinggih Gaya Bali through the implementation of digital marketing strategies. The methods used include mentoring, training, discussion, and evaluation carried out at UD Astanadi MSME, Denpasar. The results of the activities show that digital marketing, through social media and marketplaces, significantly helps MSMEs in expanding market share and building strong personal branding. In addition, digitalization provides opportunities for MSME players to reach global markets and increase competitiveness in the modern era. By integrating technology-based marketing strategies and a deep understanding of digital consumers, Balinese-style pelinggih products are expected to contribute to the growth of Bali's creative economy, while preserving ancestral cultural values.